Effect of dietary fat on blood parameters and heart rate in slightly exercised horses - Emel Gürbüz; Fatma İnal; Behiç Coşkun (Eurasian Journal of Veterinary Sciences)
Six Thoroughbred (English) horses (age 5-12 years) which exercised slightiy were used in a cross-over design trial to determine the effects of dietary (at on some blood parameters and heart rates. Two diets were formulated to meet recommended energy requirements for exercise. Experimental diet was contained %5 corn oil. Experimental periods were 23 days duration consisting ol 21 days for adaptation and 2 days for sample collection for each treatment group. During the adaptation period horses were exercised with a same rider. Blood samples were taken during the two consecutive work days exercise regime, before feeding, at rest, during the exercise, immediately after exercise and 45 minutes after exercise and subsequently analyzed for tactic acid, glucose, triglyceride and cholesterol. Heart rates also were recorded a! before and during exercise. Diets had no significant effect on blood lactic acid, glucose, triglycerides, cholesterol and heart rate in slightly exercised horses (P>0.05).